2010
DOI: 10.1364/ol.35.001810
|View full text |Cite
|
Sign up to set email alerts
|

Parallel optical monitoring of visual signal propagation from the photoreceptors to the inner retina layers

Abstract: Understanding visual signal processing can benefit from simultaneous measurement of different types of retinal neurons working together. In this paper we demonstrate that intrinsic optical signal (IOS) imaging of frog retina slices allows simultaneous observation of stimulus-evoked responses propagating from the photoreceptors to inner neurons. High resolution imaging revealed robust IOSs at the photoreceptor, inner plexiform and ganglion cell layers. While IOSs of the photoreceptor layer were mainly confined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
(15 reference statements)
2
23
0
Order By: Relevance
“…Moreover, the stimulus-evoked rod OS changes may contribute to stimulus-evoked IOS signals 45 observed in both isolated retinas, 11,17,[46][47][48] intact animals, [49][50][51] and human subjects. Comparative study of the stimulus-evoked TRP and IOS has been discussed in our previous publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the stimulus-evoked rod OS changes may contribute to stimulus-evoked IOS signals 45 observed in both isolated retinas, 11,17,[46][47][48] intact animals, [49][50][51] and human subjects. Comparative study of the stimulus-evoked TRP and IOS has been discussed in our previous publication.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows a schematic diagram of the experimental setup that has been used for intrinsic optical signal (IOS) 17,18 and TRP 10 studies in freshly isolated retinas. A high-speed camera (Neo 5.5, Andor Technology Ltd., Belfast, Ireland) was used for dynamic NIR microscopy imaging.…”
Section: Methodsmentioning
confidence: 99%
“…11 Micrometer level (<3 μm) resolution has been achieved for in vivo IOS imaging of frog retinas using custom-designed confocal 12 and OCT 13 systems. Stimulus-evoked IOSs have been observed in multiple animal models [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and human subjects. 29 Recent OCT studies revealed rapid IOS changes at photoreceptor outer segments.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 SD-OCT has been proven to allow for depth-resolved recording of IOS and to discriminate between different retinal cell populations in isolated frog retinas. 13 In living human eyes, the recording of IOS by highspeed ultrahigh resolution OCT has been possible, however, the recordings of those weak signals suffered from noise and motion artifacts. 14 In the present paper we present the preliminary results of IOS measurements in a healthy subject and two patients with retinal dystrophies, performed by a commercial SD-OCT device.…”
Section: Introductionmentioning
confidence: 99%